2014
DOI: 10.1007/s11356-014-3095-1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between air pollution, fossil fuel energy consumption, and water resources in the panel of selected Asia-Pacific countries

Abstract: The objective of the study is to examine the relationship between air pollution, fossil fuel energy consumption, water resources, and natural resource rents in the panel of selected Asia-Pacific countries, over a period of 1975-2012. The study includes number of variables in the model for robust analysis. The results of cross-sectional analysis show that there is a significant relationship between air pollution, energy consumption, and water productivity in the individual countries of Asia-Pacific. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(28 citation statements)
references
References 15 publications
6
22
0
Order By: Relevance
“…The other results indicate that there is a negative relationship between net forest depletion and CO 2 emissions, as if there is 1% increase in CO 2 emissions, net forest depletion is decreases by 0.385% points, while, there is a positive relationship between natural resource depletion and CO 2 emissions, as 1% increase in CO 2 emissions, natural resource depleted by 0.301% points. The results supported the findings of Rafindadi et al [35], Khan et al [36] etc. Rafindadi et al [35] concluded that natural resource rent and water resources both considerably increases along with increase CO 2 emissions in a panel of countries, whereas Khan et al [36] revealed that natural resource rents decreases along with increase CO 2 emissions in a short-run, while it increases subsequently with CO 2 emissions in a long-run.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The other results indicate that there is a negative relationship between net forest depletion and CO 2 emissions, as if there is 1% increase in CO 2 emissions, net forest depletion is decreases by 0.385% points, while, there is a positive relationship between natural resource depletion and CO 2 emissions, as 1% increase in CO 2 emissions, natural resource depleted by 0.301% points. The results supported the findings of Rafindadi et al [35], Khan et al [36] etc. Rafindadi et al [35] concluded that natural resource rent and water resources both considerably increases along with increase CO 2 emissions in a panel of countries, whereas Khan et al [36] revealed that natural resource rents decreases along with increase CO 2 emissions in a short-run, while it increases subsequently with CO 2 emissions in a long-run.…”
Section: Resultssupporting
confidence: 91%
“…Rafindadi et al . concluded that natural resource rent and water resources both considerably increases along with increase CO 2 emissions in a panel of countries, whereas Khan et al . revealed that natural resource rents decreases along with increase CO 2 emissions in a short‐run, while it increases subsequently with CO 2 emissions in a long‐run.…”
Section: Resultsmentioning
confidence: 99%
“…Alam et al (2015b) in a similar lines argued that financial factors are helpful to mitigate environmental concerns nationwide. Rafindadi et al (2014) examined the linkages between CO 2 emissions, water resources and natural resources in Asia-Pacific countries and concluded that these variables affected environmental sustainability agenda across the countries. Qureshi et al (2014) examined the long-run relationship between air pollution, industrialization, nuclear energy consumption, urban population and health services in Malaysia and found that environmental factors deteriorate the Malaysian health services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are some other parallel studies available on the topic as Rafindadi et al (2014) argued that fossil fuel energy consumption escalates air pollution in selected Asia Pacific countries, while Ahmed et al (2015) denounce that energy consumption, economic growth, and deforestation are linked with the environmental degradation in Pakistan. Shahbaz and Leità (2013) investigated the long-run relationship between energy demand, economic output, trade openness, and air pollution in the context of Portugal, over the period of 1970-2009.…”
Section: Introductionmentioning
confidence: 99%